Commodore Abraham Whipple of the Continental Navy : privateer, patriot, pioneer - Cohen, Sheldon S. (New perspectives on maritime history and nautical archaeology., 2010)
Sheldon Cohen's biography of Whipple presents a look inside the life of a Continental officer. He illustrates at a personal level the complexities of naval warfare, including Whipple's reliance on personal finances and family connections to outfit his ships and pay his crew. Cohen also reveals the commander's treatment as a British prisoner of war, and his eventual migration west, shedding light on experiences shared by many Revolutionary War veterans.